Structured Cabling Development in 3D Virtual Learning Environment en OpenSim - Fredy Gavilanes-Sagnay, Edison Loza-Aguirre, Byron Ernesto Vaca Barahona (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Virtual Learning Environments in 3 Dimensions can be considered a valuable tool in Education, especially in this context of Virtual Education due to the COVID-19 Pandemic, which is why after determining some problems related to this type of platform. That is why the present investigation has been guided under the Design Science Research Methodology, where the investigation has to go through the 6 phases iteratively: Identification of the problem, Design, Development, Demonstration, Evaluation, and Communication of the results. , that is why the present platform developed in OpenSim has been used for the construction of the present virtual world. The results have been evaluated using the Technologies Acceptance Model methodology. Finally, it can be determined that the results indicate that this type of platform can be considered by students as a useful tool and also that there is no greater resistance to its use due to its ease of use.